2022
DOI: 10.1038/s41598-022-12504-x
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green fluorescence image processing techniques for breast cancer macroscopic demarcation

Abstract: Re-operation due to disease being inadvertently close to the resection margin is a major challenge in breast conserving surgery (BCS). Indocyanine green (ICG) fluorescence imaging could be used to visualize the tumor boundaries and help surgeons resect disease more efficiently. In this work, ICG fluorescence and color images were acquired with a custom-built camera system from 40 patients treated with BCS. Images were acquired from the tumor in-situ, surgical cavity post-excision, freshly excised tumor and his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(51 citation statements)
references
References 36 publications
0
51
0
Order By: Relevance
“…It is obvious that the optical probes and techniques could not remove this limitation completely, but relatively increase the penetration depth compared to traditional materials and methods. It was reported that the penetration depth of the representative conventional optical probe, indocyanine green is about 4 mm [ 84 ]. Some of the introduced optical probes showed better data, but they were still below 20 mm.…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious that the optical probes and techniques could not remove this limitation completely, but relatively increase the penetration depth compared to traditional materials and methods. It was reported that the penetration depth of the representative conventional optical probe, indocyanine green is about 4 mm [ 84 ]. Some of the introduced optical probes showed better data, but they were still below 20 mm.…”
Section: Discussionmentioning
confidence: 99%
“…23 Five studies included patients who underwent neoadjuvant chemotherapy (NACT) prior to BCS or mastectomy. Unkart et al 25 included five pretreated patients out of 27, Veys et al 37 encompassed eight pretreated patients, and Kedrzycki et al 14 and Leiloglou et al 28 reported 2 out of 40 patients that had received NACT. However, only Zhang et al 32 investigated the impact of patients with NACT compared to those with primary surgery using a custom-built camera system.…”
Section: Patient Demographicsmentioning
confidence: 99%
“…Following intravenous administration, ICG interacts with plasma proteins and acts as a vascular agent allowing tissue perfusion and lymphatic drainage assessments . This fluorophore has been widely exploited in clinics for angiography and in various surgical fields, including vascular, gastrointestinal, and reconstructive surgery . More recently, ICG has been employed as an optical contrast agent in surgical oncology, and also reported as a photothermal and photosensitizer agent suitable for photothermal and photodynamic therapy in cancer treatment .…”
Section: Introductionmentioning
confidence: 99%